Evaporation and wetting behavior of silver-graphene hybrid nanofluid droplet on its porous residue surface for various mixing ratios. (June 2020) - Siddiqui, F.R.; Tso, C.Y.; Fu, S.C.; Qiu, H.H.; Chao, Christopher Y.H.
Highlights: MR-1 hybrid nanofluid droplet gives the highest evaporation rate (up to 370%). The evaporation rate increases by 240% as Vfd /Vsd increases from 1 to 20. The evaporation rate drops moving from MR-2 to MR-5 hybrid nanofluid droplets. High droplet spreading is achieved in GNP/MR-1 nanofluid/hybrid nanofluid droplets. The pore size and areal porosity increase with increasing residue size. Abstract: Droplet evaporation offers high heat rejection rates and is widely used in the form of spray cooling or dropwise cooling of various heat dissipating devices. However, due to the limiting heat flux removal capacity of conventional fluids, such as water, these cannot be used in thermal management of high heat flux devices. In this research, the evaporation of silver (Ag)-graphene (GNP) hybrid nanofluid droplet and its residue effects on the evaporation of following Ag-GNP hybrid nanofluid droplet, due to its synergistic thermal properties, is experimentally investigated for various mixing ratios, from MR-1 (0.1(Ag):0.9(GNP)) to MR-5 (0.9(Ag):0.1(GNP)), and different residue sizes. A theoretical model is also proposed for hybrid nanofluid droplet evaporation and semi-empirical relations are developed to estimate the hybrid nanofluid droplet spreading over its residue surface. The results show a substantial increase in the droplet evaporation rate with increasing residue size and decreasing mixing ratio. MR-1 hybrid nanofluid droplet gives the highest evaporation rate (up to 370%) on its highly wetted residue surface, while the evaporation rate significantly drops moving from MR-2 to MR-5 hybrid nanofluid droplets on their partially wetted residue surfaces. Moreover, the evaporation rate substantially increases (up to 240%) with increasing residue size for MR-1 hybrid nanofluid droplet resting on its residue surface, however, the effect of residue size on droplet evaporation rate considerably diminishes moving from MR-2 to MR-5 hybrid nanofluid droplets resting on their respective residues. Graphical abstract: Image, graphical abstract